A New Study Method Protection Safety Equipment Overload Electronic Device - Ahmad Aqil Munawa; Muhammad Ahyar; Tigor Maruli Tua Nasution; Alwi Risky; Rahman Aulia; Solly Aryza (Jurnal Scientia, 2024)
The relay safety device on the prepaid Kwh meter functions as a power limiting protection system to prevent damage to the prepaid Kwh meter relay caused by power consumption exceeding the registered power. Where in this study describes the device to be designed, the code security method automatically cuts off the electric current if the power used exceeds the registered power so that this method can reduce damage to the Kwh relay for customers. The results of testing the designed tool show a difference in the percentage of calculations. For the iron, the percentage of error in the calculation results is 1.99%, while for testing the water heater, the percentage of error is 0.53% due to the lack of sensitivity of the PZEM-004T sensor in reading the load used. The voltage measured at the output of the designed tool reaches 205 V. The test measurement of the tool designed based on SNSU PK.P-02:2020 - National Tolerance Standardization Agency shows an error in measuring digital measuring instruments, namely ±5%. If it exceeds the specified rules, the results cannot be used or referred to because they are not appropriate.